2019
DOI: 10.1021/acs.est.9b00014
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effect of Migration Strategy on Pollutant Occurrence in Eggs of Arctic Breeding Barnacle Geese (Branta leucopsis)

Abstract: Arctic-breeding geese acquire resources for egg production from overwintering and breeding grounds, where pollutant exposure may differ. We investigated the effect of migration strategy on pollutant occurrence of lipophilic polychlorinated biphenyls (PCBs) and protein-associated poly-and perfluoroalkyl substances (PFASs) and mercury (Hg) in eggs of herbivorous barnacle geese (Branta leucopsis) from an island colony on Svalbard. Stable isotopes (δ 13 C and d 15 N) in eggs and vegetation collected along the migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…However, these studies measured OHCs in plasma, and how comparable these results are to the egg concentrations in the present study is unknown. A recent study from the Baltic Proper found that in eggs of marine birds PCBs and DDTs concentrations were orders of magnitude higher than those of PFASs (De Wit et al, 2020), whereas in eggs of terrestrial arctic barnacle goose ( Branta leucopsis ) mean ∑PFAS equalled ∑PCBs (Hitchcock et al, 2019). Thus it remains difficult to draw firm conclusions about the expected proportional relationship between OCs and PFASs in bird eggs because so few studies have compared these in the same samples and none, to our knowledge, on a long‐term temporal scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies measured OHCs in plasma, and how comparable these results are to the egg concentrations in the present study is unknown. A recent study from the Baltic Proper found that in eggs of marine birds PCBs and DDTs concentrations were orders of magnitude higher than those of PFASs (De Wit et al, 2020), whereas in eggs of terrestrial arctic barnacle goose ( Branta leucopsis ) mean ∑PFAS equalled ∑PCBs (Hitchcock et al, 2019). Thus it remains difficult to draw firm conclusions about the expected proportional relationship between OCs and PFASs in bird eggs because so few studies have compared these in the same samples and none, to our knowledge, on a long‐term temporal scale.…”
Section: Resultsmentioning
confidence: 99%
“…The deviation of the mean concentrations reported in the earlier study (Bustnes et al, 2007) with the mean of the recent samples was low, 16% ( R 2 = 0.69) and 22.5% ( R 2 = 0.70), for the PCBs and p,p′ ‐dichlorodiphenyldichloroethylene ( p,p′‐ DDE), respectively. The NILU carried out the OC analyses for the period 2010–2019 (see Hitchcock et al, 2019 for details).…”
Section: Methodsmentioning
confidence: 99%
“…Every type of sample was analyzed at least in duplicate to ensure precision of the measurements. The detection limit of the instrument was 0.05 ng [49].…”
Section: Analysis Of Contaminantsmentioning
confidence: 95%
“…Indeed, for many decades, one of the main affluents of Lake Maggiore, River Toce, has received wastewaters from a chemical factory, which produced technical DDT by using a chlor-alkali plant with mercury cells [50,57], located in Pieve Vergonte, about 20 km from Lake Mergozzo. Currently, soils in the River Toce basin, which is bordering on the Lake Mergozzo catchment, are contaminated with DDT and p,p -DDD by atmospheric deposition from the industrial area [49], and their run-off can represent a possible source of contamination for the water bodies in that area together with direct atmospheric transport and deposition. Alternatively, we cannot exclude that some fish species such as roach migrate from Lake Maggiore to Lake Mergozzo, exploiting a connecting stream between the two lakes.…”
Section: Chemicals Concentrations In Biota Of Lake Mergozzomentioning
confidence: 99%
“…A consideration when using seabird eggs as a contaminant monitoring matrix is the origin of the egg constituents (Hitchcock et al 2019b). Depending on the reproductive life history strategy, females can invest a greater degree of stored energy (capital breeding), or energy recently acquired (income breeding) in reproduction (Stephens et al 2009).…”
Section: Blood and Eggs As Monitoring Matrices Of Legacy And Emergingmentioning
confidence: 99%